Essential functions, syntheses and detection of sialyl Lewis X on glycoproteins - Qiushi Chen; Han Liu; Xuechen Li (Exploration of Drug Science)
It is widely acknowledged that sialyl Lewis X (sLeX), the composition and linkage of which are N-acetylneuraminic acid (Neu5Ac) α2-3 galactose (Gal) β1-4 [fucose (Fuc) α1-3] N-acetylglucosamine, is usually attached to the cell surface. It presents as a terminal structure on either glycoproteins or glycolipids and has been demonstrated to be related to various biological processes, such as fertilization and selectin binding. Due to the vital role of sLeX, its synthesis as well as its determination approaches have attracted considerable attention from many researchers. In this review, the focus is sLeX on glycoproteins. The biological importance of sLeX in fertilization and development, immunity, cancers, and other aspects will be first introduced. Then the chemical and enzymatic synthesis of sLeX including the contributions from more than 15 international research groups will be described, followed by a brief view of the sLeX detection focusing on monosaccharides and linkages. This review is valuable for those readers who are interested in the chemistry and biology of sLeX.